2017
DOI: 10.1590/s1806-92902017000300002
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the mode of reproduction of bahiagrass hybrids using cytoembryological analysis and molecular markers

Abstract: -The aim of this study was to determine the mode of reproduction of a hybrid progeny derived from intraspecific crosses of Paspalum notatum through cytoembryological analysis and use of RAPD (random amplification of polymorphic DNA) molecular markers. Cytoembryological analysis allowed identification of the mode of reproduction of 28 plants that were selected after agronomic productivity evaluations. Of these, 19 had embryo sac morphology compatible with an apomictic mode of reproduction and nine had embryo sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Progenies of 198 hybrid plants were established for agronomic assessment and the 28 most productive plants in terms of herbage accumulation and production of leaves were selected. Cytoembryological analyses and molecular markers were used to assess the reproduction mode of the hybrids, indicating segregation for apomictic and sexual genotypes (Weiler et al 2017), also reported by Kumar et al (2010b) and Kumar et al (2017) in Cenchrus ciliaris, which reinforces the possibility of producing apomictic cultivars with desirable traits and using sexual genotypes as mother plants in future crosses. Barbosa et al (2019) established them in lines and evaluated in two physiographic regions of Rio Grande do Sul (Central Depression and Campain), showing the productive potential of some of these genotypes.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Progenies of 198 hybrid plants were established for agronomic assessment and the 28 most productive plants in terms of herbage accumulation and production of leaves were selected. Cytoembryological analyses and molecular markers were used to assess the reproduction mode of the hybrids, indicating segregation for apomictic and sexual genotypes (Weiler et al 2017), also reported by Kumar et al (2010b) and Kumar et al (2017) in Cenchrus ciliaris, which reinforces the possibility of producing apomictic cultivars with desirable traits and using sexual genotypes as mother plants in future crosses. Barbosa et al (2019) established them in lines and evaluated in two physiographic regions of Rio Grande do Sul (Central Depression and Campain), showing the productive potential of some of these genotypes.…”
Section: Introductionsupporting
confidence: 62%
“…The sexual to apomictic ratio of the genotypes was 1.2:1, close to the expected 1:1 for tetrasomic monogenic inheritance with dominant apospory. In other evaluations of the reproductive mode of segregating P. notatum hybrid progenies, were found sex:apo ratios of 2.8:1 (Martínez et al 2001); 6.5:1 (Stein et al 2004); 4.6:1 and 4.3:1 in the first and second generations, respectively (Acuña et al 2011) and 1:2.1 (Weiler et al 2017). Some results showed a distortion, trending to a deviation towards sexual reproduction.…”
Section: Evaluations Of the Reproduction Modementioning
confidence: 90%
“…The mode of reproduction (apomictic or sexual) of the selected hybrids was evaluated using cytoembryological analysis and molecular markers (Weiler et al, 2017). Once the agronomical value of the apomictic genotypes is confirmed, they will be registered and protected as cultivars, and sexual plants with high productivity may remain in the program to be used as a female parent in future crossings.…”
Section: Resultsmentioning
confidence: 99%
“…The most direct and traditional form to study the reproduction mode is the observation of the embryo sacs and the processes of the megagametogenesis pathway (Koltunow, ). Among the Paniceae tribe, some of the apomictic pathways are detectable by microscopy methods by observing embryo sacs (Acuña, Martínez, & Quarin, ; Chapman & Busri, ; Kozub et al., ; Kumar, Chandra, Gupta, & Shukla, ; Naumova, Hayward, & Wagenvoort, ; Ortiz et al., ; Philipson, ; Quarin, ; Quarin & Burson, ; Quarin & Hanna, ; Warmke, ; Weiler et al., ). However, diplospory could be difficult to differentiate from sexual ones (Meier, Zappacosta, Selva, Pessino, & Echenique, ).…”
Section: Introductionmentioning
confidence: 99%